Phylogenetic relationships of the North-eastern Atlantic and Mediterranean forms of Atherina (Pisces, Atherinidae) - Francisco, S. M. (2014)
The genus Atherina (Sand-smelts) is distributed in the Eastern Atlantic Ocean and Mediterranean Sea, extending south along the African coast into the Indian Ocean (Quignard and Pras, 1986). It is a genus of small inshore fishes with many populations living in brackish and freshwater. The taxonomy of the genus has been troublesome due to the intraspecific variability of some of its species, the overlap of characters among many of them and because many nominal species were apparently described based on individuals originating from different localities.